The Effect of Financial Compensation and Work Environment on Employee Satisfaction and Performance CV. Amri Jaya Dinamika of Pekanbaru City - Kasman; Agus Seswandi (SAINS ORGANISASI, 2022)
This study aims to determine and analyze the effect of Financial Compensation and Work Environment on job satisfaction and employee performance. To find out and analyze the effect on job satisfaction. The effect of financial compensation and work environment on performance through job satisfaction and the effect of satisfaction on employee performance. The data sources of this research are primary data and secondary data. With 105 employees as the research sample. The data analysis used in this study is PLS Structural Equation Modeling (SEM) which is operated through the SmartPLS program. The results showed that financial compensation and work environment had an effect on job satisfaction and employee performance. Financial compensation and work environment have a significant effect on employee performance through employee job satisfaction. Employee job satisfaction has a significant effect on employee performance.